Effect of sintering temperature and AR glass addition towards physical properties of porcelain clay for sewer pipes application - Hanapi, Muhammad Ikhmal; Ahmad, Sufizar; Taib, Hariati; Chee, Chen Tan (Penerbit UTHM, 2018)
The current work is aimed to investigate significant phase changes at certain sintering temperature with addition of Alkali Resistant (AR) glass in manufacturing clay pipes for sewer application. The use of porcelain clay reinforced with milled AR fiberglass (3 wt%, 6 wt%, 9 wt% and 12 wt%) was determined in this study. Both of raw materials were turned into powder to conduct thermal analysis and produce compact samples. The powder was compacted by uniaxial pressing technique to examine the volume shrinkage. Volume shrinkage analysis was done by measuring the dimension of green body and sintered sample (900°C, 1000°C 1100°C and 1200°C). The image of microstructural morphology was observed by Scanning Electron Microscope. Thermogravimetric graph indicates large amount of mass loss found to be 75% between 450°C to 800°C for porcelain and all mixtures. While Differential Thermal graph reveals the endothermic shift was produce at 250°C. The maximum volume shrinkage was obtained at 1200°C which is 31.7% with 3 wt% AR glass addition. The microstructural image proved the correlation to volume shrinkage. The presence of glassy phase demonstrates the phenomenon of fluxing agent melts and bonding with porcelain where shrinking particle takes place to construct dense sample.